Evaluation of the use of tissue expander in a university service - Kethelyn Keroline Telinski Rodrigues; Maria Cecilia Closs Ono; Jean Raitz Novais; Isabella Correa de Oliveira; Heloize Callegari Menegazzo; Renato da Silva Freitas (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: Tissue expansion is an important reconstruction method to solve defects such as burns and giant nevi or breast reconstruction. This article aims to report the experience of the Plastic Surgery Service of the Hospital de Clínicas of the Federal University of Paraná (UFPR) with the use of expanders. Methods: This is a retrospective, descriptive, and analytical study of patients who underwent tissue expansion for reconstructive surgery at the Hospital de Clínicas da UFPR, from January 2010 to December 2016. Results: 61 patients and 80 surgeries were analyzed, including re-expansion procedures. Age ranged from 2 to 73 years (mean 31). The majority of patients were female (83.6%), aged over 40 years, undergoing breast reconstruction treatment after radical mastectomy (36%). The complications observed in these patients were: signs of infection (14.7%), suture dehiscence (3.2%), seroma (3.2%), defect in the expander (3.2%), exposure of the expander (3, 2%), necrosis (1.6%) and signs of hypoperfusion (1.6%). Patients undergoing breast reconstruction had the highest number of complications (40.1%). Reexpansion was necessary for 37.7% of patients. Conclusion: The skin expansion technique is indicated for several pathologies' treatment. The tissue expansion procedure has high complication rates. Knowing the patient's profile, the main types of complications, and the factors associated with these complications can help prevent them.